2004
DOI: 10.1103/physrevlett.92.114301
|View full text |Cite|
|
Sign up to set email alerts
|

Vibration-Induced Granular Segregation: A Phenomenon Driven by Three Mechanisms

Abstract: The segregation of large spheres in a granular bed under vertical vibrations is studied. In our experiments we systematically measure rise times as a function of density, diameter and depth; for two different sinusoidal excitations. The measurements reveal that: at low frequencies, inertia and convection are the only mechanisms behind segregation. Inertia (convection) dominates when the relative density is greater (less) than one. At high frequencies, where convection is suppressed, fluidization of the granula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(53 citation statements)
references
References 27 publications
5
47
0
1
Order By: Relevance
“…Not only in nature and our daily lives, segregation of particles is also of great importance to the processing of powders in industries [36]. In the past two decades, there has been an upsurging number of laboratory experiments to unveil the mechanism of the segregation driven by vertical vibrations or rotation [37][38][39][40][41][42][43]. Counterintuitively, it has been found that large light particles might sink under vertical vibrations while in the meanwhile equally sized heavy particle rises [44][45][46].…”
Section: Segregationmentioning
confidence: 99%
“…Not only in nature and our daily lives, segregation of particles is also of great importance to the processing of powders in industries [36]. In the past two decades, there has been an upsurging number of laboratory experiments to unveil the mechanism of the segregation driven by vertical vibrations or rotation [37][38][39][40][41][42][43]. Counterintuitively, it has been found that large light particles might sink under vertical vibrations while in the meanwhile equally sized heavy particle rises [44][45][46].…”
Section: Segregationmentioning
confidence: 99%
“…The wellknown "Brazil nut problem," in which a large particle (the so-called intruder) rises relative to the surrounding smaller-sized granular material when vertically vibrated, has been studied extensively by experiments, theoretical models, and numerical simulations. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In a vibrating granular bed, the segregation may also be influenced by the vibration conditions, bed height, ambient pressure, humidity, size ratio, density ratio, restitution coefficient, and the friction coefficient of the particles. 8,9,12,16 Granule segregation in a vertically-vibrated granular bed is highly complicated and much remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, heterogeneous mixtures commonly undergo segregation, a phenomenon of great interest for materials processing [6]. Segregation of binary mixtures also occurs in the laboratory, in vibrating bed [7,8] and rotating drum experiments [9][10][11][12][13][14][15][16][17][18][19][20][21][22], and upon pouring into a Hele-Shaw cell [23][24][25]. It can be caused by differences in particle size, shape, smoothness, or density.…”
mentioning
confidence: 99%